Educação a distância e trabalho docente virtual: sobre tecnologia, espaços, tempos, coletividade e relações sociais de sexo na Idade Mídia - Daniel Ribeiro Silva Mill (2006)
School time and space both constitute foundational factors for the comprehension of the pedagogical work process. This leads to reflection about the logic space-time which guides the organization of school work. As educational space and time are relevant, there is much to think about classroom space (historically understood as a privileged place for teaching and learning and also for the teaching role) and the emerging virtual environments for learning (simulated teaching-learning environment by Internet). There is also much to understand about fragmented educational time in assigned moments for playtime, history classes, mathematics classes, etc, and the flexible times of the Education in Media Ages Contemporary times lack in reflections on four basic factors of the educational process: teaching, learning, management and techno-pedagogical mediation, that is, there is a lack of analysis of teachers, learners, managers and technologies responsible for the teaching and learning mediation. This research intended to contribute to the first factor: teaching. Either directly or not, the three other factors were covered; especially means (technologies) of distance education teachers work mediated by Internet (information and communication technologies). Thus, the leading questions of this investigation were: What kind of transformations can be observed in the educators work when pedagogical processes can be established by means of virtual technologies? How changes in time and space produced by virtual pedagogical processes can influence teachers work? What kind of implications are these? These questions arose from the following assumption: the work process in virtual education seemed to establish new time and space for the teacher and this restructured space and time would be affecting not only everyday work or the educators teaching practice, but also its nature as a work class. From these preoccupations, this research was proposed, aiming at analyzing implications by teachers work due to space and times changes introduced by virtual pedagogical processes. Related to this objective, various categories of analysis were studied such as, space-time, technology, teachers work, genre, distance education, collective work, leisure, production and reproduction, among others. The following hypothesis was considered for this study: the new forms to experiment time and space in Media Ages, concerning work, occur due to the intensified work processes and the precarious work relations. As a result, this thesis presented: a) a general analysis about the organizational pattern that distance education has been taking in Brazil, in which the role of virtual tutors was highlighted in the organizational structure: Who is the distance education worker?; b) a theoretical mapping of the diverse and contradictory theories about space and time conceptions, emphasizing space and time work and specifying space and time in virtual work process in a capitalist context: How space and time are regarded in Media Ages?; c) a characterization of virtual tutors as telecommuters, showing some appealing aspects and dangers of this new organizational form of educational workers: These teaching telecommuters are subjected to which benefits, risks and dangers?, d) an analysis of the relationship among work, technology and genre, considering distance education mediated by information and communication technologies as a field of investigation: As technologies are sexed, which differentiations could be observed between male and female work in telecommuting teaching?; e) a survey of gains and losses of the implementation of pedagogical work by Internet: In work and education terms, how could evident benefits in collective work of presential education be observed in telecommuting teaching; f) a reflection about the advantageous and disadvantageous possibilities of telecommuting teaching: How long distance teachers make use of time and space in their everyday practices?; and finally g) a theoretical and practical exercise (methodological proposal), beyond the central theme of this research paper (work, technology and education), about the possibilities of a new occupation for the Internet in academic and scientific areas. How to use the Internet to collect data for scientific researches? The results obtained in this nvestigation can be considered satisfactory. Now, the necessity of carrying out more studies about the four factors in the educational process, including teaching and means of the teachers work can be quite noticed. Reflections about distance education in times of converging media are needed. What are the implications of this new space and time context for learning, management, and teaching and for the technological mediation in Education in contemporary times?